2022
DOI: 10.1128/spectrum.00448-22
|View full text |Cite
|
Sign up to set email alerts
|

Changing Predominance of Norovirus Recombinant Strains GII.2[P16] to GII.4[P16] and GII.4[P31] in Thailand, 2017 to 2018

Abstract: In the present study, the prevalence of norovirus infection in children with acute gastroenteritis in Chiang Mai, Thailand between 2017 and 2018 was 14.9%. A variety of norovirus genotypes were detected, including GI.5, GII.2, GII.3, GII.4, GII.6, GII.7, GII.13, GII.14, and GII.17 with the predominance of GII.4 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…So far, 11 different NoV recombinant patterns have been identified, including GII.1[P33], GII.2[P16], GII.3[P16], GII.3[P21], GII.4[P12] GII.4[P16], GII.4[P31], GII.6[P7], GII.12[P33], GII.13[P16], and GII.14[P7]. The emergence of NoV GII.2[P16] recombinant strains during 2016–2017 was reported in many countries worldwide as well as Thailand 11,19,31–33 . The follow‐up surveillance in Chiang Mai, from 2017 to 2018, demonstrated that the predominance of GII.2[P16] in 2017 was replaced by GII.4[P16] and GII.4[P31] in 2018 19 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, 11 different NoV recombinant patterns have been identified, including GII.1[P33], GII.2[P16], GII.3[P16], GII.3[P21], GII.4[P12] GII.4[P16], GII.4[P31], GII.6[P7], GII.12[P33], GII.13[P16], and GII.14[P7]. The emergence of NoV GII.2[P16] recombinant strains during 2016–2017 was reported in many countries worldwide as well as Thailand 11,19,31–33 . The follow‐up surveillance in Chiang Mai, from 2017 to 2018, demonstrated that the predominance of GII.2[P16] in 2017 was replaced by GII.4[P16] and GII.4[P31] in 2018 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Recombination is one of the mechanisms that contribute a major role to the evolution and genetic diversity of NoV. Investigation of NoV recombinant strains circulating in pediatric patients with AGE in Chiang Mai has been carried out continually from 2005 to 2018 18,19 . So far, 11 different NoV recombinant patterns have been identified, including GII.1[P33], GII.2[P16], GII.3[P16], GII.3[P21], GII.4[P12] GII.4[P16], GII.4[P31], GII.6[P7], GII.12[P33], GII.13[P16], and GII.14[P7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations